EFEKTIVITAS ASAP CAIR DARI PIROLISIS TEMPURUNG KELAPA SEBAGAI PESTISIDA ORGANIK DALAM PENGENDALIAN HAMA PADA TANAMAN HIDROPONIK DI KELURAHAN TERJUN, KECAMATAN MEDAN MARELAN - Sari, Nurmala; Razali, Mariany; Sari Br Sijabat, Octanina; Hidayat Sihotang, Supran; Rizki Sembiring, Fanny; Putra Gulo, Penyabar; Yanti Laia, Fenida (Mejuajua: Jurnal Pengabdian pada Masyarakat, 2025)
Hydroponic cultivation is increasingly popular in urban areas due to its efficiency and hygiene. However, pest attacks remain a major obstacle, often addressed by the use of chemical pesticides. Long-term use of chemical pesticides negatively impacts health, and in hydroponic farming, they can leave harmful residues and negatively impact the environment. Utilizing coconut shell waste as an organic pesticide is an innovation that supports environmentally friendly agriculture. This program aims to use liquid smoke produced from the pyrolysis process of coconut shells as an organic pesticide to control pests in hydroponic plants in Terjun Village, Medan Marelan District. The activity stages are carried out using participatory and educational methods, including preparation, implementation, and evaluation. The preparation stage includes site surveys, coordination with partners, and preparation of educational materials and leaflets. During the implementation stage, socialization, demonstrations of organic pesticide application in the form of liquid smoke, and distribution of leaflets are conducted. The evaluation stage was conducted through a questionnaire test before and after the activity (pre-test and post-test) to assess the increase in participants' understanding. The final evaluation results showed an average increase in participants' knowledge of 32.6%, from a pre-test score of 62.4% to a post-test score of 95.0%. The highest increase occurred in the understanding of liquid smoke and its functions by (+ 43%), followed by an increase in the aspect of knowledge about organic pesticides by (+ 40%) and interest in using liquid smoke by (+ 35%).